Mild depolarization of the inner mitochondrial membrane is a crucial component of the mechano-chemiosmotic mechanism of coupling - Eldar A. Kasumov; Ruslan E. Kasumov; Irina V. Kasumova (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
The human body receives the main energy in the form of ATP (about 50 kg per day), mainly by oxidative phosphorylation in the mitochondria, and a small part from glycolysis. It has been recognized a long ago that several major human diseases (2 type diabetes, cancer, heart diseases, etc.), and aging are associated with mitochondrial dysfunction. Mitochondrial dysfunction causes a dramatic fall of ATP production and an increase in ROS production.